Bioeconomic Models and the Formative Evaluation of Fisheries-Related Programs - Ian Graham Cahill; Éric Robard (The Evaluation Center at Western Michigan University, 2014)
Background: Bioeconomics combines methods from the biological study of living resources, particularly population dynamics, with methods of economic analysis. Most applications have been in program design for resource management. Although formative evaluations often deal with potential improvements to design based on examination of the program at some point in the early or middle period of its life, there has been little interplay between bioeconomic modelling and evaluation of programs in the context of fisheries management programs. Purpose: This paper describes the potential synergy between the analytic modelling techniques from bioeconomics and the formative evaluation of programs that support sustainable fisheries.   Setting: NA Intervention: We focus on how feedback from qualitative formative evaluation methods could be used to improve the development and use of realistic bioeconomic models to inform program design, which would in turn improve formative evaluation. Research Design: NA Data Collection and Analysis: NA Findings: NA Keywords: bioeconomic models; formative evaluation; fisheries-related programs